Amotosalen‐HCl‐UVA pathogen reduction does not alter poststorage metabolism of soluble CD40 ligand, Ox40 ligand and interkeukin‐27, the cytokines that generally associate with serious adverse events. Issue 2 (21st October 2014) - Hamzeh‐Cognasse, H.; Laradi, S.; Osselaer, J. C.; Cognasse, F.; Garraud, O.
<x xml:space="preserve">Abstract</x> Platelets in therapeutic platelet concentrates are commonly acknowledged to release biologically active constituents during storage. This study examined the influence of photochemical pathogen reduction treatment (PRT) using amotosalen‐HCl and UVA light vs. untreated control platelet components, on three factors recently reported to be associated with serious adverse events associated with platelet component (PC) transfusions: sCD40L, IL‐27 and sOX40 ligand. Levels of such cytokine‐like factors increased significantly during storage, but no significant difference was detected between PRT‐ and control PCs. This suggests that occurrences of AEs are not directly influenced by PRT but rather may depend on alternate determinants.